1951
DOI: 10.1161/01.cir.3.2.282
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of the Coronary Arteries during Life

Abstract: By retrograde catheterization of the carotid or the brachial arteries small polyethylene or woven catheters have been inserted into the ascending aorta in 10 individuals. Diodrast or Neo-Iopax solution was forcibly injected and serial roentgenograms were rapidly taken. The coronary arteries or branches were demonstrated in 5 of the subjects. Similar studies were made in 5 dogs with normal hearts, and also in 10 dogs in whom a coronary artery had previously been obstructed. In certain of the normal animals not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

1951
1951
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Further refinements in 1951 led to a paradigm shift in diagnosing improvement in clinical coronary disease in men. 21 Selective coronary angiography, first reported by its innovator, Mason Sones, at the Xth International Congress of Radiology in 1962 greatly advanced clinical angiographic correlations. 22 Because of these technological advances, cardiologists eventually had a firm basis for making specific diagnoses and recommending individualized treatments.…”
mentioning
confidence: 99%
“…Further refinements in 1951 led to a paradigm shift in diagnosing improvement in clinical coronary disease in men. 21 Selective coronary angiography, first reported by its innovator, Mason Sones, at the Xth International Congress of Radiology in 1962 greatly advanced clinical angiographic correlations. 22 Because of these technological advances, cardiologists eventually had a firm basis for making specific diagnoses and recommending individualized treatments.…”
mentioning
confidence: 99%
“…Jonsson et al (1951), discussing thoracic aortography for the demonstration of patent ductus arteriosus and coarctation, state that the catheter tip "may fasten in the orifice of one of the coronary arteries, with perhaps fatal results." Helmsworth et al (1950) reported their attempts at coronary arteriography in six patients, two of whom died following repeated injection of contrast medium. As DiGuglielmo and Guttadauro (1952) indicate in their monograph on coronary arteriography, such repeated injections constitute a series of periods of myocardial anoxia.…”
mentioning
confidence: 99%
“…It will be noted in figure 5 that three veins were selected crossing the fibrous ring and included in the model, while only two were incorporated in the model shown in figure 6. In both instances many additional arterial and venous vessels were present in the serial sections but were omitted to facilitate the mechanics of model construction and preserve simplicity.…”
mentioning
confidence: 99%
“…This model, made from the heart of a 6 month old fetus and comprising 90 In figure 8, we have rearranged a schema based on the work of Wearn, Mettier, Klumpp and Zschiesche35 to demonstrate the relations of the described sinusoids and common bundle (see figures 5 and 6) to the remainder of the tions the blood flow might well be in a reverse direction to that now indicated by the broken lines in figure 8. For example, it is interesting to speculate that such a reversal of flow may account, for the low incidence of heart block observed following the gradual occlusion of the coronary arteries.…”
mentioning
confidence: 99%